Strategy Analysis Of SMEs Business Development (Case Study On Junggo Village Goat Goat Subdistrict Prigen, Pasuruan, East Java Province, Indonesia) - Hamdan Suriyok (LPPM of NAROTAMA UNIVERSITY, 2017)
The purpose of this study was to identify internal and external factors of SMEs of Junggo Village Goat, to analyze the strengths, weaknesses, opportunities and threats faced by Junggo Goat Village SMEs, to formulate a business development strategy that should be done of SMEs of Goat Village Junggo . This research uses participatory action research (PAR) approach to data collection and processing. The data obtained in the form of primary data and secondary data. Based on the results of SWOT matrix analysis, there are several alternative strategies such as increasing the number of permanent customers, increasing sales capacity, increasing production capacity, promoting, performing financial and administration recording system, conducting market research and development, providing quality goats, increasing synergism and partnership, provide supplementary food and preventive medicine and conduct comparative studies.